2019
DOI: 10.3390/cancers11111695
|View full text |Cite
|
Sign up to set email alerts
|

Dual PDK1/Aurora Kinase A Inhibitors Reduce Pancreatic Cancer Cell Proliferation and Colony Formation

Abstract: Deregulation of different intracellular signaling pathways is a common feature in cancer. Numerous studies indicate that persistent activation of the phosphoinositide 3-kinase (PI3K) pathway is often observed in cancer cells. 3-phosphoinositide dependent protein kinase-1 (PDK1), a transducer protein that functions downstream of PI3K, is responsible for the regulation of cell proliferation and migration and it also has been found to play a key role in different cancers, pancreatic and breast cancer amongst othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The other study showed that combined MK-0457 and Nutlin-3 treatment activated p53dependent postmitotic checkpoints at pseudo-G1 phase and induced proapoptotic p53 signaling and mitochondrial apoptosis in AML [216]. Other molecules, such as SRC [217], CHEK1 [218], mTOR [219,220], WEE1 [221], PDK1 [222,223], and MEK [224], have also been chosen as targets together with AURKA in preclinical studies.…”
Section: Combination Of Akis With Targeted Therapiesmentioning
confidence: 99%
“…The other study showed that combined MK-0457 and Nutlin-3 treatment activated p53dependent postmitotic checkpoints at pseudo-G1 phase and induced proapoptotic p53 signaling and mitochondrial apoptosis in AML [216]. Other molecules, such as SRC [217], CHEK1 [218], mTOR [219,220], WEE1 [221], PDK1 [222,223], and MEK [224], have also been chosen as targets together with AURKA in preclinical studies.…”
Section: Combination Of Akis With Targeted Therapiesmentioning
confidence: 99%
“…For zebrafish xenografts, wild type Tübingen (TU) zebrafish were bred and maintained in the Western Australian Zebrafish Experimental Research Centre (Biomedical Research Facility- Shenton Park, Western Australia). Experiments and data analyses were done as previously described [ 32 ]. Briefly, HPAF-II human pancreatic cancer cells were incubated with Vibrant™-Dil dye (ThermoFisher Scientific) 4 μL/mL in HBSS at 37 °C for 10 min, followed by 15 min on ice in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…Six to seven-week-old NOD/SCID (NOD.CB17-Prkdcscid/Arc) immune-deficient mice were purchased from the Animal Resources Centre (ARC-Murdoch-Western Australia) and maintained under pathogen-free conditions with water and food provided ad libitum. Mice were injected subcutaneously randomly on either the left or the right flank with 3.5 × 10 6 HPAF-II human pancreatic cancer cells following a previously described protocol [ 32 ]. When tumours reached a volume of about 50 mm 3 (according to the formula: tumour volume = 1/2(length × width 2 ), mice were randomized into two groups and treated with either vehicle (0.5% carboxymethyl cellulose (CMC)/0.4% Tween-80) or JVG045 30 mg/kg as a daily intra-peritoneal injection (IP) in a volume of 250 μL.…”
Section: Methodsmentioning
confidence: 99%
“…For zebra sh xenografts, wild type Tübingen (TU) zebra sh were bred and maintained in the Western Australian Zebra sh Experimental Research Centre (Biomedical Research Facility-Shenton Park, Western Australia). Experiments and data analyses were done as previously described (32). Brie y, HPAF-II human pancreatic cancer cells were incubated with Vibrant™-Dil dye (ThermoFisher Scienti c) 4μL/mL in HBSS at 37°C for 10 minutes, followed by 15 minutes on ice in the dark.…”
Section: Zebra Sh Xenograftsmentioning
confidence: 99%